2016
DOI: 10.1016/j.envint.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between study sponsorship, risks of bias, and research outcomes in atrazine exposure studies conducted in non-human animals: Systematic review and meta-analysis

Abstract: Background A critical component of systematic review methodology is the assessment of the risks of bias of studies that are included in the review. There is controversy about whether funding source should be included in a risk of bias assessment of animal toxicology studies. Objective To determine whether industry research sponsorship is associated with methodological biases, the results, or conclusions of animal studies examining the effect of exposure to atrazine on reproductive or developmental outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…What becomes particularly difficult to self‐regulate is the convergence of cognitive bias, a human nature to seek to please one's patron, and the interests of one's employer or client. For instance, studies funded by drug or medical device makers tend to find positive effects that favor the company funding the research (Lexchin et al ; Smith ), and the funding effect for studies of chemical toxicity may lean toward finding negative effects (Krimsky , ; Bero et al ). However, concordance between a funder's self‐interest and research findings does not alone indicate bias.…”
Section: The Interested Scientist: Conflicts Of Interest Competing Imentioning
confidence: 99%
See 2 more Smart Citations
“…What becomes particularly difficult to self‐regulate is the convergence of cognitive bias, a human nature to seek to please one's patron, and the interests of one's employer or client. For instance, studies funded by drug or medical device makers tend to find positive effects that favor the company funding the research (Lexchin et al ; Smith ), and the funding effect for studies of chemical toxicity may lean toward finding negative effects (Krimsky , ; Bero et al ). However, concordance between a funder's self‐interest and research findings does not alone indicate bias.…”
Section: The Interested Scientist: Conflicts Of Interest Competing Imentioning
confidence: 99%
“…They termed this distortion of information to further what may be perceived to be righteous ends as "white hat bias" (Cope and Allison 2009). However, their conflicted financial backing from the soft drink industry and from manufacturers of baby formula contributed to countercriticisms of funding bias (Bes-Rastrollo et al 2014;Harris and Patrick 2011;Mandrioli et al 2016). Unresolved in the claims and counterclaims of bias and financial conflicts of interest was what advice was most credible.…”
Section: Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmaceutical, tobacco, food, or chemical industry funding biases human research studies towards outcomes that are favorable to the sponsor’s product, even when controlling for other biases in the methods [78,1011,17]. Thus, even when the methods meet high standards for internal validity, financial conflicts of interest may influence research results through other mechanisms, such as the framing of the question, how the study is actually conducted, and whether it is fully and accurately reported.…”
Section: Why Financial Conflicts Of Interest Are So Problematicmentioning
confidence: 99%
“…Articles have examined financial COIs and sources of funding in research on the safety of industrial chemicals, 16,17 pesticides, 18 genetically modified foods, 19 sugar-sweetened beverages, 20 endocrine-disrupting compounds, 4,21 and electronic cigarettes. 22 Friedman and Friedman recently conducted a study of 373 articles published in 17 highly-cited environmental or occupational health journals in 2012.…”
Section: Introductionmentioning
confidence: 99%